Titanium alloy particles formation in electrical discharge machining and fractal analysis - Khilji, Irshad Ahamad; Siti Nadiah, Mohd Saffe; Pathak, Sunil; Ţălu, Ştefan; Kulesza, Slawomir; Bramowicz, Miroslaw; Venugopal Jayarama, Reddy (Springer Link, 2022)
A large amount of material is machined by electrical discharge machining (EDM) and the machined debris is flushed away as waste. The present study aims to establish EDM as a top-down method which can effectively machine hard-to-cut materials while the by-product, i.e., metal debris, can be utilized as micro/nano particles. In the present work, titanium-alloy grade 5 was machined using a die-sink EDM and the debris was collected from the dielectric fluid with a multistage filtration system. The collected debris was cleaned and the particles were characterized. Particles were examined by scanning electron microscopy, x-ray diffraction, and energy-dispersive x-rays to determine size, shape, and chemical crystal structure. The average size of the formed particles was 5.14 µm and they were spherical. A fractal analysis was performed on the SEM images to deepen the study of the formed particles.